INTRAVENOUS IMMUNOGLOBULIN THERAPY FOR KAWASAKI DISEASE (CASE REPORT) - Bintoro Adi Saputro; Ramzi Syamlan (JURNAL DARMA AGUNG, 2023)
Kawasaki disease (KD) is acute vasculitis with an unidentified cause. The prevalence of Kawasaki disease is greater in developed countries or regions, also known as developed areas. Throughout 2021, two cases of complete Kawasaki were identified at Perkebunan Jember Klinik Hospital. Using a Harada score of 3, intravenous immunoglobulin (IGIV) treatment screening was calculated. In general, IGIV is used to reduce the risk of abnormalities/damage to the coronary arteries. The purpose of this study is to identify the diagnostic criteria and indications for administering IGIV to children with Kawasaki disease. Qualitative Method with the case report approach. Patients diagnosed with Kawasaki disease must receive therapy and care based on their symptoms and conditions. Kawasaki disease can be treated with a number of different drugs. IGIV can be delivered to Kawasaki disease patients as a form of treatment. IGIV treatment based on Harada Score. Kawasaki disease is a condition that is rarely recognized by the general public. The resulting conclusions are as follows Complete Kawasaki disease is diagnosed by five days of persistent fever plus 4 of the 5 classic symptoms. Screening with a scoring system is needed in making decisions about giving IGIV.